The effectiveness of incorporating chest proprioceptive neuromuscular facilitation with conventional chest physical therapy in Kartagener’s syndrome: a case report - Nidhi Yadav; Farah; Sahar Zaidi; Kajal Kumari (MGM Journal of Medical Sciences)
Kartagener’s syndrome (KS) is a rare autosomal recessive genetic disorder primarily characterized by impaired ciliary function, leading to respiratory complications. Developing a specialized, tailored physiotherapy protocol for managing KS is urgently necessary. The primary aim of this study was to determine whether incorporating chest proprioceptive neuromuscular facilitation (PNF) along with conventional chest physiotherapy offers additional benefits for patients with KS. A 13-year-old male presented with chronic nasal congestion, difficulty breathing through the nose, fatigue, and a severe cough. Clinical and imaging assessments confirmed the presence of situs inversus, bronchiectasis, dextrocardia, ethmoid sinusitis, and digital clubbing. He was treated with oral antibiotics, mucolytics, and chest physiotherapy. Following this treatment, there was improvement in his symptoms, and he was prescribed a continuous low-dose prophylactic antibiotic regimen. After implementing physical therapy interventions, that is, chest PNF (perioral pressure, intercostal stretch, vertebral pressure, co-contraction of the abdomen, maintenance of manual pressure, and anterior stretch-lifting of the basal area) along with conventional chest physiotherapy (active cycle of breathing, forced expiratory techniques, postural drainage, and diaphragmatic scoop), significant improvements were observed in pulmonary function, including enhanced inspiratory capacity, chest expansion, and key spirometric parameters such as FEV₁, FEV₁/forced vital capacity (FVC), and FVC. This case study highlights the potential advantages of integrating chest PNF techniques into conventional chest physiotherapy for managing KS. The findings suggest incorporating PNF may enhance airway clearance, improve respiratory function, and optimize pulmonary mechanics. The observed improvements in the breathing patterns and secretion mobilization indicate that PNF could be a valuable adjunct to standard therapy, particularly for patients with chronic respiratory conditions such as KS.